Inheritance of some Flower Traits in Patch Petal Dendrobium Orchids - Wannakrairoj, Surawit; Rattamanee, Chakkrapong (Agriculture and Natural Resources, 2012)
Dendrobium is the most important tropical orchid. Patch coloration on petals is a novel trait for cultivar improvement of the genus. The trait was obtained from somaclonal variances of both cutﬂ ower and potted plant cultivars. Most of the variance is male-sterile. Hybrids between the variants and the wild-type cultivars yielded some progenies with patch petals. Genetic analysis on the inheritance of some ﬂ ower traits of the variance was performed. Only a cross between both parents with patch petals could be produced from Dendrobium Anucha Flare ’Suriyon’ × D. Ekapol ’Annie’, the only male-fertile mutant. From the segregating populations, it was proposed that a dominant M allele controls the pinkish purple coloration and a recessive m allele controls the white coloration on sepals. For petal color, a dominant C allele was conﬁ rmed to control the pinkish purple and a recessive c allele controls the white. Importantly, dominant alleles in ﬁ ve loci were found to be essential for the petal patch coloration in this study. In addition, it was postulated that the El allele controls the enlarge labellum while the el allele controls the normal labellum.